2000
DOI: 10.1002/(sici)1096-9071(200006)61:2<235::aid-jmv10>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus reactivation associated with diminished cell-mediated immunity in Antarctic expeditioners

Abstract: Epstein-Barr virus (EBV) reactivation and cell-mediated immune (CMI) responses were followed in 16 Antarctic expeditioners during winter-over isolation at 2 Australian National Antarctic Research Expedition stations. Delayed-type hypersensitivity (DTH) skin testing was used as an indicator of the CMI response, that was evaluated 2 times before winter isolation and 3 times during isolation. At all 5 evaluation times, 8 or more of the 16 subjects had a diminished CMI response. Diminished DTH was observed on ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
46
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(51 citation statements)
references
References 23 publications
4
46
0
1
Order By: Relevance
“…The gammaherpesvirus Epstein-Barr virus is sensitive to stress-induced glucocorticoids (4,24,35,41,67,68), and the present studies suggest that KSHV might also reactivate during stress-induced autonomic nervous system activity. The emergence of stress-reactive biology in all major classes of Herpesviridae suggests a potential evolutionary advantage for latent viruses to monitor organismal stress levels, which could be diagnostic of reduced cellular immune threat (28,54,72) or lowered host-transmission hurdles (9,69).…”
Section: Vol 79 2005supporting
confidence: 54%
“…The gammaherpesvirus Epstein-Barr virus is sensitive to stress-induced glucocorticoids (4,24,35,41,67,68), and the present studies suggest that KSHV might also reactivate during stress-induced autonomic nervous system activity. The emergence of stress-reactive biology in all major classes of Herpesviridae suggests a potential evolutionary advantage for latent viruses to monitor organismal stress levels, which could be diagnostic of reduced cellular immune threat (28,54,72) or lowered host-transmission hurdles (9,69).…”
Section: Vol 79 2005supporting
confidence: 54%
“…12 Studies of Abbreviations used GEE: General estimating equations HDBR: Head-down bed rest IL-1RA: IL-1 receptor antagonist Kv: K value uX-174: Bacteriophage uX-174 sTNFR1: Soluble TNF receptor 1 plasma cytokine balances in these and other study subjects revealed evidence of T-cell activation events, possibly in response to shedding of Epstein-Barr virus (EBV). [12][13][14][15] In the current investigation we assessed the ability of adult female subjects to respond appropriately to immunization with uX-174 and concomitantly measured their plasma cytokine levels.…”
mentioning
confidence: 99%
“…Several studies have connected lytic activity and reactivation with rejection episodes in transplant recipients (3,8), posttransplant lymphoproliferative disorder (PTLD) (20,23,33), and clinical disease activity in patients with multiple sclerosis (34). Immunosuppression seems to trigger not only reactivation but also physically or psychologically challenging situations that result in diminished cell-mediated immunity (6,14,18).…”
mentioning
confidence: 99%